The Influence of Internal Locus of Control, Spiritual Intelligence, Financial Literacy, and Lifestyle on Personal Financial Management Behavior - Fauzah, Risma; Rahmawati, Ika Yustina; Tubastuvi, Naelati; Alfalisyado, Alfalisyado (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2026)
This study aims to analyze the effects of internal locus of control, spiritual intelligence, financial literacy, and lifestyle on students' personal financial management behaviour in Purwokerto. The population consisted of active students at Universitas Muhammadiyah Purwokerto, Universitas Islam Negeri Saifuddin Zuhri, and Universitas Jenderal Soedirman. The research sample was selected using proportional random sampling. The data used is quantitative data gathered through a Google Forms-based questionnaire, which was distributed to students through social media. This study involved 100 respondents, whose number was determined with the use of the Slovin formula. Data analysis was conducted using SmartPLS 3 to identify relationships among variables. Measurement model testing through Outer Loading, Discriminant Validity, Construct Reliability and Validity, R Square, and then continued with hypothesis testing. The analysis results revealed that internal locus of control, financial literacy, and lifestyle significantly affect personal financial management behaviour, while spiritual intelligence does not show an effect that is significant effect on personal financial management behaviour. The findings provide a new perspective on the influencing factors for students’ financial decisions and deepen our understanding regarding the aspects that affect their financial management behaviour.